2011
DOI: 10.1021/jm200577a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Tetrahydroisoquinoline-Based Hydroxamic Acid Derivative (ZYJ-34c) as Histone Deacetylase Inhibitor with Potent Oral Antitumor Activities

Abstract: Histone deacetylase (HDAC) has emerged as an attractive target for the development of antitumor agents during the past decade. Previously tetrahydroisoquinoline-bearing hydroxamic acid analogue, ZYJ-25e (1), was identified and validated as a potent histone deacetylase inhibitor (HDACi) with marked in vitro and in vivo antitumor potency. In the present study, further modification of 1 led to another more potent, orally active HDACi, ZYJ-34c (4). Compared to FDA-approved drug suberoylanilide hydroxamic acid (SAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Three dimensional structures suggest that only minor variations to a linear alkyl chain, analogous to the lysine side chain, would fit into the tubular groove. However, commonly reported linkers include triazole, isoxazole, tetrahydroisoquinoline and phthalamides [90,[94][95][96]. Shen et al incorporated a putative -stacking triazole ring into the linker and found 25 to have the best selectivity of 14 compounds examined for inhibition of HDAC1 (IC 50 104 nM) over HDAC8 ( Table 1) [94].…”
Section: Linker Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three dimensional structures suggest that only minor variations to a linear alkyl chain, analogous to the lysine side chain, would fit into the tubular groove. However, commonly reported linkers include triazole, isoxazole, tetrahydroisoquinoline and phthalamides [90,[94][95][96]. Shen et al incorporated a putative -stacking triazole ring into the linker and found 25 to have the best selectivity of 14 compounds examined for inhibition of HDAC1 (IC 50 104 nM) over HDAC8 ( Table 1) [94].…”
Section: Linker Modificationsmentioning
confidence: 99%
“…Furthermore, the acyclic amide 33 showed decreased inhibitor potency, suggesting that the ideal conformation has the lactam carbonyl constrained to the plane of the aromatic ring [90]. Compounds 34 and 35, containing a tetrahydro-isoquinoline in the linker, were 4-fold and 2.5-fold respectively more selective for HDAC8 (IC 50 47 nM and 68 nM) over HDAC6 (IC 50 191nM and 163 nM) ( Table 1) [96]. Ligand docking in the HDAC8 crystal structure suggested two hydrogen bonds between the carbonyl oxygen of proline 273 and the amide NH and free amino group (Fig.…”
Section: Linker Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In brief, 10 lL of Hela nuclear extracts was mixed with 0.0097, 0.039, 0.39, 1.56, 6.25, 25 lM of target compounds (50 lL) and SAHA, and then they were incubated for 30 min, using 100% and none HDACs groups as control group. Five minutes later, fluorogenic substrate Boc-Lys (acetyl)-AMC (40 lL) was added, and the mixture was incubated at 37°C for 30 min and then stopped by addition of 100 lL of developer containing trypsin and TSA.…”
Section: In Vitro Inhibition Of Hela Cells Extracts Fluorescence Assaymentioning
confidence: 99%
“…A series of tetrahydroisoquinoline-based hydroxamic acid derivatives was discovered by Zhang et al as HDAC inhibitor with in vivo antitumor potency in a human breast carcinoma xenograft model [138]. The carboxamide group is part of the pharmacophore [139], but this group is not presented in the structures of EDL-291 and EDL-155. A series of tetrahydroisoquinoline amide substituted phenyl pyrazoles are reported to be selective Bcl-2 inhibitors [140].…”
Section: Discussionmentioning
confidence: 99%